(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Tuvans are an indigenous Turkic-speaking ethnic group of Southern Siberia, distinguished by a high level of preservation of folklore, in particular, folk songs. The article presents a new form of publication of Tuvan song folklore in a multimedia format, which is the result of the work on the project “Song Tradition of the Ovyur Tuvans of the 21st Century in the Context of Rural-Urban Migration”, implemented with the support of the Russian Scientific Ford.